Respuesta :

The functions are inverse function because (d) [tex]\sqrt{g(x) -5} + 4[/tex]

How to determine the inverse statement?

The functions are given as:

[tex]f(x) = \sqrt{x -5} + 4[/tex]

[tex]g(x) = (x - 4)^2 + 5[/tex]

If the functions are inverse functions, then

f(g(x)) = x

Start by calculating f(g(x)), as follows:

[tex]f(x) = \sqrt{x -5} + 4[/tex]

[tex]f(g(x)) = \sqrt{g(x) -5} + 4[/tex]

This gives

[tex]f(g(x)) = \sqrt{(x - 4)^2 + 5 -5} + 4[/tex]

Evaluate the difference

[tex]f(g(x)) = \sqrt{(x - 4)^2} + 4[/tex]

Evaluate the exponent

f(g(x)) = x - 4 + 4

Evaluate the difference

f(g(x)) = x

Hence, the functions are inverse function because [tex]\sqrt{g(x) -5} + 4[/tex]

Read more about inverse functions at:

https://brainly.com/question/14391067

#SPJ1